The Development of Snakes and Ladders Game-Based Learning Media on the Topic of Vibrations and Waves Using Google Slides for Junior High School Students - Fadillah, Nur; Abdul Wahid, Mulyadi; Nengsih, Sri (Universitas Islam Negeri Ar-Raniry, 2024)
The topic of Vibrations and waves is considered challenging for students. The subject must be delivered with good strategies and supported by good learning media. The purpose of this study is to develop an alternative learning media based on the classic Snakes and Ladders game using Google Slides for the topic of Vibrations and Waves at the junior high school level. The development steps of the media were adapted from the design model of Alessi and Trollip, which consists of three stages, including (1) planning, (2) design, and (3) development. In the development phase, six reviewers participated in the product evaluation. Three of them are as media experts and the others are as material experts. After evaluating the product, reviewers provided remarks and scores for each evaluation aspect. Overall, the product received an 86.87% score for the media aspect and a 92.06% score for the material aspect, both categorized as very feasible. These results indicate that the Snakes and Ladders game-based learning media on the topic of Vibrations and Waves using Google Slides is very feasible for use in the teaching and learning process for junior high school students.